KODE PEMBACAAN DALAM ANTOLOGI CERPEN CINTA TAK PERNAH TUA KARYA BENNY ARNAS: SEMIOTIKA ROLAND BARTHES - Amaliyah, Milah Rizki; Supena, Ahmad (Universitas Batanghari, 2024)
The research was conducted to reveal, dismantle, analyze and describe the five reading codes of Roland Barthes in the short story anthology Cinta Tak Perna Tua by Benny Arnas. In achieving this goal, researchers used qualitative descriptive methods with observation techniques and note-taking techniques. The researcher made observations by carefully reading the poetry anthology book by Benny Arnas, then breaking up the words into lexias containing reading codes. This reveals the results of the discovery of all Roland Barthes reading codes in the three short stories used as research samples, the results include (1) the hermeneutical code is a code that contains puzzles so that it makes the reader wonder, this code is found on pages 40, 91, and 111 ; (2) semic code is a code that refers to a sign to convey a connotative meaning that is different from the original meaning, this code is found on pages 42, 97, 113; (3) proaretic code is a code that refers to a character's actions to convey a message to the reader, this code is found on pages 41, 94 and 113; (4) cultural code is a code that refers to the culture of the short story writer or the background of the short story, this code is found on pages 42, 94 and 117; (5) symbolic code is the use of signs that can represent something more profound, this code is found on pages 45, 95, 114. These reading codes show that there is a deeper meaning in a short story, there are many implied meanings in every sign, code and symbol in the short story text that is difficult to interpret if it does not go through the analysis stage first.